Hepatic resection for recurrent hepatocellular carcinoma during pregnancy: a case report - Maeda, Takashi (Surg Case Rep, 2020)
BACKGROUND: Hepatocellular carcinoma (HCC) during pregnancy is extremely rare. Treatment strategies for cancers detected during pregnancy have been controversial. We herein report a case of recurrent HCC detected at 20 weeks of pregnancy, which subsequently prompted hepatic resection after abortion. CASE PRESENTATION: A 36-year-old woman underwent laparoscopic partial hepatectomy for HCC (20 mm in diameter) in segment 5 of the liver during follow-up after being determined as a hepatitis B virus carrier two and a half years ago. Post-surgery follow-up abdominal ultrasonography revealed a 36-mm tumor in segment 7 of the liver. Abdominal contrast-enhanced computed tomography revealed a well-enhanced tumor with a 40-mm diameter in segment 7 adjacent to the inferior vena cava and right hepatic vein, suggesting HCC recurrence. Laboratory data revealed total bilirubin (0.4 mg/dL), aspartate aminotransferase (28 IU/L), alanine aminotransferase (30 IU/L), glutamyltransferase (16 IU/L), prothrombin time (115.3%), and indocyanine green retention rate at 15 min (7.0%). α-Fetoprotein (AFP) (12,371.5 ng/mL; normal range < 10 ng/mL) and PIVKA-II (208 mAU/mL; normal range < 40 mAU/mL) were both significantly elevated. After discussions with a cancer board consisting of experts from the departments of gastroenterology, obstetrics and gynecology, and surgery, as well as obtaining appropriate informed consent from the patient and her family, we decided to perform a hepatic resection after abortion. Subsequently, abortion surgery was performed at 21 weeks and 2 days of pregnancy. After 6 days, subsegmentectomy of liver segment 7 was performed under general and epidural anesthesia, with a pathological diagnosis which was moderately differentiated HCC being established. Given the good postoperative course, without particular complications, the patient was subsequently discharged 10 days after the operation. Approximately 2 years after the surgery, the patient remains alive without recurrence, while both AFP and PIVKA-II were within normal limits. CONCLUSIONS: Treatment strategies for HCC detected during pregnancy remain controversial. As such, decisions should be made based on HCC growth and fetal maturity after thorough multidisciplinary team discussions and obtaining appropriate informed consent from the patient and her family.